"É possível aprender inglês na escola?": crenças de professores e alunos sobre o ensino de inglês em escolas públicas - Hilda Simone Henriques Coelho (2005)
This study, in three public schools in Zona da Mata, Minas Gerais state aimed at (a) detecting the beliefs about English language teaching in public schools of four English teachers and their students and (b) understanding how these teachers and students justify their beliefs about the teaching and learning of English. The theoretical framework was based on studies about beliefs (Nespor, 1987; Pajares, 1992; Barcelos, 2001), teacher education (Barcelos, 1995; Oliveira 2001) and English teaching in Brazil (Félix, 1999; Rolim, 1998; Oliveira, 2002). The chosen methodology was case study and the following data collection instruments were used: narratives, class observations, questionnaires, and interviews. The results have indicated that the teachers beliefsreflect what they think is possible to do in teaching English in their schools, what they believe to be their role and how they perceive public schools. Some of these beliefs are based on their learning histories and their teaching experiences. The students show in their beliefs what they expect from English teaching and base their beliefs on their experiences as learners, on what they believe is possible to happen in public schools and on what they hear from their teachers and peers experiences. In short, the results have suggested that teachers believe they are responsible for their students learning and that it is possible to teach only basic structures within a program that has as main focus language for specific purposes. Students believe that teaching should happen following a sequence, beginning in the first grades of elementary school in order to give them better knowledge in the language. This study has shown the need to know teachers and students expectations and thus, re-signify English teaching in public schools.